Arbeidsters in een confectie-atelier. Kopie van exemplaar van Dir. Gen. van de Arbeid, Den Haag, nr.32797
Arbeidsters in een confectie-atelier. Kopie van exemplaar van Dir. Gen. van de Arbeid, Den Haag, nr.32797.